2–18 GHz balanced antipodal Vivaldi conformal phased array antenna with resistive load and shorting posts. Issue 11 (16th August 2022) - Chen, Ming Zhe; Wang, Hong Bin; Cheng, Yu Jian
Abstract: In this paper, a 2–18 GHz balanced antipodal Vivaldi conformal phased array antenna is proposed. Firstly, the conformal array achieves a low profile of 0.11 λ Low by using the tightly coupling mechanism. Here, the gap‐induced element resonance (GIER) and the common mode resonance occur in the operating band, limiting the impedance bandwidth. Thus, the resistors are loaded to eliminate the GIER by suppressing the resonant current. Furthermore, the shorting posts are used to remove the common mode resonance by decreasing the resonant length. A transition structure between the stripline (SL) and the ground coplanar waveguide (GCPW) is designed to feed the antenna. The simulated results show that the array achieves a 9:1 bandwidth (2–18 GHz) for active VSWR <2.5 at broadside. Besides, the active VSWR is less than 2.5 for ±60° scanning in E‐plane and 3.8 for ±45° scanning in H‐plane. A 12 × 8 array prototype is fabricated and measured to validate the performance of the array. The measured results show a good agreement with the simulation.